Smell and Taste in Severe CoViD-19: Self-Reported vs. Testing - Mazzatenta, Andrea; Neri, Giampiero; D'Ardes, Damiano; De Luca, Carlo; Marinari, Stefano; Porreca, Ettore; Cipollone, Francesco; Vecchiet, Jacopo; Falcicchia, Chiara; Panichi, Vincenzo; Origlia, Nicola; Di Giulio, Camillo (Frontiers in Medicine, 2020)
One of the most striking reported symptoms in CoViD-19 is loss of smell and taste. The frequency of these impairments and their specificity as a potential CNS function biomarker, are of great interest as a diagnostic clue for CoViD-19 infection as opposed to other symptomatologic similar diseases, and because of their implication in viral pathogenesis. Here severe CoViD-19 was investigated by comparing self-report vs. testing of smell and taste, thus the objective severity of olfactory impairment and their possible correlation with other symptoms. Because a significant discrepancy between smell and taste testing vs. self-report results p < .001 emerges in our result, we perform statistical analysis highlight disagreement among normosmia p < .05; hyposmia, severe hyposmia and anosmia p < .001; and in hypogeusia, severe hypogeusia, while no differences are in normogeusia and ageusia. Therefore, we analyzed olfactory threshold by objective test reveal the distribution of hyposmic (34%), severe hyposmic (48%) and anosmic (13%) patients in severe CoViD-19. In severe CoViD-19 patients’ taste is lost in 4.3% of normosmic, in 31.9% of hyposmic, in 46.8% of severe hyposmic and in 17% of anosmic. 95% of one hundred CoViD-19 patients objective tested were affected by smell dysfunction, while taste 47%. Further, analysis by objective testing also highlighted that the severity of smell dysfunction in CoViD-19 subjects did not correlate with age and sex. In conclusion, we report by objective testing that the majority of CoViD-19 patients report severe anosmia, that most of subjects have olfactory impairment rather than taste one, finally that the olfactory impairment correlate with symptoms onset and hospitalization, p<.05. Patients exhibits severe olfactory impairment has been hospitalized in about a week from symptoms onset, double time is occurred in subjects with normosmia. Our results may be limited by the relatively small number of study participants, but suggest by objective testing that hyposmia, severe hyposmia and anosmia may relate directly to infection severity and neurological damage. The smell test assessment could be a potential screening symptom that might contribute to the decision to test suspected cases or guide quarantine instructions, further therapeutic approach and evaluation of neurological damage.